Fundamental principles behind plasmon-induced processes in polarizable systems - Kuda Singappulige, Gowri Udayangani (Kansas State University, 2021)
Plasmonic materials enhance light-induced processes because they can accumulate a plethora of energy in a wide range of the electromagnetic spectrum. Understanding the natural laws that govern the plasmon-induced processes such as plasmon decay and photocatalysis remains a challenge due to the ultrafast dynamics of plasmons. Real-time propagation techniques with a quantum mechanical description of electrons in molecules and materials has become a valuable tool to mimic such processes and investigate the dynamical pathways. In this thesis, we explore the plasmon decay mechanisms and the effect of light-related parameters on photocatalytic dissociation of molecules using time-dependent density functional theory. We identified a decay of the plasmon-like excited state in the tetrahedral Ag₈ cluster within tens of femtoseconds after the resonant external electric field is turned off. The time-dependent off-diagonal density matrix elements, Pov (t), demonstrated that while the single-particle transitions that are responsible for the excited state of interest decline, new transitions start to grow in the absence of the electric field. It was remarkable that these newly emerging transitions oscillate with twice the incident frequency, as evident from the energy domain off-diagonal elements, Pov (ω), Our work on larger tetrahedra, octahedra, and nanorods discovered nonlinear optical enhancement in silver nanoparticles regardless of their size and shape, which arises as a result of plasmon decay. Up to four-photon absorptions were detected in some cases. Additionally, well-separated excited states with a strong oscillator strength appear to decay faster, while a dense manifold of excited states leads to coupling between the closely lying neighboring states. We also examined the effect of nuclear vibrations on the decay of the plasmon-like peak in naphthalene. We found that certain normal modes induce a decay of the dipole response within a few hundreds of femtoseconds. Interestingly, the time-dependent difference density indicates for the first time that a dark electronic state, which lies close in energy to the resonant state, results in this decay. Finally, we present a study on the effect of various electric field parameters including the field strength, polarization direction, and the nature of the excited state on the photodissociation of an oxygen molecule that is bound to a plasmonic silver nanocluster. We observed a strong dependence of the field strength on the photodissociation of oxygen. In addition, the light that was polarized along the direction of charge transfer tended to increase the O-O bond breaking.
Keywords: Plasmon decay; Nonlinear optical properties; Real-time time-dependent density functional theory; Silver nanoclusters